NA TEIA DA EDUCAÇÃO AMBIENTAL: FORMAÇÃO DE PROFESSORES NA PERSPECTIVA DA COMPLEXIDADE - Antonio, Juliana Mara (2018)
Although the EA has begun, in Brazil, with the conservative side, with time has intensively inserted the social question to the environment. Since then, research in this field has begun to be based on theories of philosophical origin already consolidated in education as Hermeneutics, Phenomenological and Critical. Another theory that has recently been debated is that of Edgar Morin's Complexity. It offers a broad theoretical framework to aggregate aspects of approaches and theories that are found in isolation. Thus, our objective was to analyze the possible theoretical-practical subsidies for the EA based, mainly, in the work The Seven Knowledge Needed to the Education of the Future. This analysis occurred during the construction and application of a continuing training course in EE for teachers. The method was an exploratory study with participant observations and qualitative analysis approach, since it aimed to enable a better interaction with the subjects involved in the process. The participants were 18 teachers from different areas in Early Childhood Education and Primary Education I and II in a private school in a municipality in the state of Paraná. The teachers participated in a continuous training course with a 40-hour workload. We used as a research tool a questionnaire structured before the course and one after the course to verify possible changes in teachers' perception and understanding about AS. For analysis of the data we used the Discourse Analysis of Orlandi (2004). The results show that the conservative and pragmatic conceptions of AD initially prevailed and, in the course of the process, there was an expansion of these visions, especially about the Seven Wisdom connected with AD. Besides the construction of new knowledge and knowledge, it was also thought about selfcriticism and the need for constant reform. Some teachers showed that they had a critical view about the environment, but that the course contributed to increase this criticality for other aspects related to human formation. We consider that the Complexity Theory contributes to realize that education and science are intrinsically related in our culture, so that thinking education is inseparable from thinking the sciences and other modes of expression of knowledge.